Testing astrophysical models for the PAMELA positron excess with cosmic ray nuclei. - Mertsch, P; Sarkar, S (2009)
The excess in the positron fraction measured by PAMELA has been interpreted as due to annihilation or decay of dark matter in the Galaxy. More prosaically it has been ascribed to direct production of positrons by nearby pulsars or due to pion production during diffusive shock acceleration of hadronic cosmic rays in nearby sources. We point out that measurements of secondary cosmic ray nuclei can discriminate between these possibilities. New data on the titanium-to-iron ratio support the hadronic source model above and enable a prediction for the boron-to-carbon ratio at energies above 100 GeV.